Identification of Pollutant Sources of PM2,5 and PM10 in Waru, Sidoarjo, East Java - Gita Pati Humairoh; Arie Dipareza Syafei; Muhayatun Santoso (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Air pollution have a very detrimental effect, not only for humans but also impact on the ecosystem of animals and plants. In this study, we will examine air pollution in March 2019 around Waru, Sidoarjo, East Java through research on air particulate concentrations with the size of PM2.5 and PM10. This study aims to determine the estimation of the origin of pollution around the Waru, Sidoarjo, East Java so that can be used as a scientific reference as a step to make the right decisions and policies in overcoming the effects of pollution. The data processing method in this study is with use the Conditional Probability Function (CPF) method to find out the estimated source the origin of pollution is based on meteorological data (speed and wind direction). The highest measurement results obtained at PM2.5 concentration was 24.13 μg/m3 still fulfilling the daily quality standards set by Goverment Regulations No. 41/1999 and WHO, whereas at PM10 concentration was 66.53 μg/m3 still met the daily quality standards has been established Goverment Regulations No. 41/1999 but has exceeded the quality standards set by WHO. While the results of the analysis of the CPF Method are obtained from the original source pollutants for PM2.5 come from vehicle activities on the highway, while the source of pollutants for PM10 comes from industrial activities.